Getting to the Roots: A Developmental Genetic View of Root Anatomy and Function From Arabidopsis to Lycophytes - Augstein, Frauke (Front Plant Sci, 2018)
Roots attach plants to the ground and ensure efficient and selective uptake of water and nutrients. These functions are facilitated by the morphological and anatomical structures of the root, formed by the activity of the root apical meristem (RAM) and consecutive patterning and differentiation of specific tissues with distinct functions. Despite the importance of this plant organ, its evolutionary history is not clear, but fossils suggest that roots evolved at least twice, in the lycophyte (clubmosses and their allies) and in the euphyllophyte (ferns and seed plants) lineages. Both lycophyte and euphyllophyte roots grow indeterminately by the action of an apical meristem, which is protected by a root cap. They produce root hairs, and in most species the vascular stele is guarded by a specialized endodermal cell layer. Hence, most of these traits must have evolved independently in these lineages. This raises the question if the development of these apparently analogous tissues is regulated by distinct or homologous genes, independently recruited from a common ancestor of lycophytes and euphyllophytes. Currently, there are few studies of the genetic and molecular regulation of lycophyte and fern roots. Therefore, in this review, we focus on key regulatory networks that operate in root development in the model angiosperm Arabidopsis. We describe current knowledge of the mechanisms governing RAM maintenance as well as patterning and differentiation of tissues, such as the endodermis and the vasculature, and compare with other species. We discuss the importance of comparative analyses of anatomy and morphology of extant and extinct species, along with analyses of gene regulatory networks and, ultimately, gene function in plants holding key phylogenetic positions to test hypotheses of root evolution.